Knowledge, awareness, and attitude among practicing dentists about teledentistry in Indore, Central India - Swati V Balsaraf; Revant H Chole (Wolters Kluwer Medknow Publications, 2015)
Introduction: Telemedicine is a rapidly forming subset of health informatics. Until now, no studies are documented on the knowledge, awareness, and attitude of practicing dentists on teledentistry. Aim: To conduct a survey among the practicing dentist regarding knowledge, awareness and attitude among practicing dentists about teledentistry in Indore, Central India. Materials and Methods: A cross-sectional questionnaire study was conducted among the practicing dentists from April 2014 to July 2014 in Indore. The sample size of 142 dentists was selected through convenience sampling. Chi-square test was used for the association. Results: Overall 121 dentists had heard about teledentistry. Internet was recorded as the most common source of obtaining information about teledentistry. In this study, almost 20 BDS dentists said that teledentistry is useful in oral medicine and radiology. Conclusion: Most of the dentists were aware of teledentistry, and the practicing dentists are aware of working technique, uses and advantages and disadvantages of teledentistry. Until date, no teledentistry projects in India, although there are few telemedicine projects run by the Government of India. There are a lot of gray areas in teledentistry to be worked on.